DIGITAL LIBRARIES: FACILITATING ACCESS TO INFORMATION AND DEVELOPING LIBRARY SERVICES USING MODERN TECHNOLOGIES - Khujaeva Nigora Ahmadovna (Scholar Express Journal, 2025)
Digital libraries have become an integral part of modern Information Society. They provide people with convenient, fast and efficient access to information resources available worldwide. Digital libraries, formed on the basis of the Internet and other high technologies, are tasked with converting information from physical to digital and making it widely available to users. These libraries are distinguished from traditional libraries by their systematic organization and large information bases. In this way, digital libraries are not only bringing revolutionary changes in the provision of library services, but also radically updating the methods of obtaining and managing information.
Keywords: libraries; information; internet